Turning point from economies of scale to quality enhancement: a marketable quality and profitability model for corporations. (5th June 2007) - Barolli, Valbona; Fukuda, Heihachiro; Barolli, Leonard; Takizawa, Makoto
In this paper, we present a model to extract the turning point from economies of scale to enhancement of marketable quality. We apply the real values of some leading manufacturing corporations in Japan to our proposed model to analyse its accuracy. By analysis, we found that the theoretical and real standard values of the marketable quality indicator for the rate of operation at the break event point were both 0.6. We evaluated the proposed model and verified that the fair relationship better reflects the real economical situation of corporations than the unfair relationship. The proposed model gives a good approximation of the economical trends of corporations.